Gender differences through the lens of Rio: Australian Olympic primetime coverage of the 2016 Rio Summer Olympic Games. (August 2019) - Xu, Qingru; Billings, Andrew C; Scott, Olan K M; Lewis, Melvin; Sharpe, Stirling
This study explored gender differences within the Australian primetime broadcast of the 2016 Rio Summer Olympic Games. Forty-five broadcast hours from the Seven Network were examined regarding clock-time, name mentions, and descriptions divided by biological sex, finding that the Seven Network devoted nearly equal clock-time to male and female athletes, yet 14 of the top 20 most mentioned athletes (70%) were men. In terms of word-by-word descriptors, gender differences were also uncovered on many levels relating to attributions of athletic success, failure, personality, and physicality. The findings of this study suggest that—at least within an Australian sports context—gender portrayals ranged from relative equality to significant differences depending on the metric employed. Theoretical and practical implications are provided.